Lipoxin A4 Suppresses Estrogen-Induced Epithelial–Mesenchymal Transition via ALXR-Dependent Manner in Endometriosis. (April 2018) - Wu, Rong-Feng; Huang, Zhi-Xiong; Ran, Jing; Dai, Song-Juan; Lin, Dian-Chao; Ng, Tai-Wei; Chen, Qing-Xi; Chen, Qiong-Hua
Objective: Epithelial–mesenchymal transition (EMT) is essential for embryogenesis, fibrosis, and tumor metastasis. Aberrant EMT phenomenon has been reported in endometriotic tissues of patients with endometriosis (EM). In this study, we further investigated the molecular mechanism of which lipoxin A4 (LXA4 ) suppresses estrogen (E2 )-induced EMT in EM. Study Design: The EMT markers were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot in eutopic endometrial epithelial cells (EECs) or investigated by immunohistochemistry and qRT-PCR in endometriotic lesion of EM mice. The invasion and migration under different treatments were assessed by transwell assays with or without Matrigel. The messenger RNA (mRNA) and activities of matrix metalloproteinase 2 (MMP-2) and MMP-9 were determined by qRT-PCR and gelatin zymography, respectively. Luciferase reporter assay was used to measure the activity of zinc finger E-box binding homeobox 1(ZEB1) promoter. The level of E2 in endometriotic tissues was assessed by enzyme-linked immunosorbent assay. Results: In eutopic EECs, stimulatory effects of E2 on EMT progress, migration, and invasion were all diminished by LXA4 . Lipoxin A4 reduced E2 -induced ZEB1 promoter activity. Lipoxin A4 also attenuated the phosphorylation of extracellular signal-regulated kinase and p38 mitogen-activated protein kinase induced by E2 . Co-incubation with Boc-2 rather than DMF antagonized the influence of LXA4 . Animal experiments showed that LXA4 inhibited the EMT progress, MMP expression, and proteinase activities of endometriotic lesion in an LXA4 receptor (ALXR) manner, which suppressed the progression of EM. ZEB1 mRNA expression was upregulated and well correlated with E2 level in human endometrium. Conclusion: Lipoxin A4 suppresses E2 -induced EMT via ALXR-dependent manner in eutopic EECs, which reveals a novel biological effect of LXA4 in EM.